Research Progress in Modification of Nickel-Rich Ternary Cathode Material LiNi0.8Co0.1Mn0.1O2 for Lithium Ion Batteries - Li, Chun Li; Xie, Zhi Li; Ding, Jie; Zhu, Hong Ru; Ma, Xue Zhi (Materials science forum, 2021)
In order to increase the energy density of lithium-ion battery, the LiNi0.8Co0.1Mn0.1O2(NCM811) cathode material with higher Ni content has attracted much attention due to its advantages such as high energy density, low cost. However, there are some bottleneck problems about the NCM811 such as capacity fading, harsh storage conditions, poor thermal stability, poor safety, which limit its large-scale commercial use. This article reviews the urgent problems for NCM811 high nickel ternary materials, briefly describes several common synthesis methods, and focuses on the modification methods, such as element doping, surface coating and special core-shell structure for enhancing the electrochemical performances and explain the modification mechanism. Finally, we prospect the possible research development and commercial application of high nickel ternary material.